2011
DOI: 10.1519/jsc.0b013e318212e23b
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rest Interval Length on Multi and Single-Joint Exercise Performance and Perceived Exertion

Abstract: The purpose of this study was to compare repetition performance and rating of perceived exertion (RPE) with 1-, 3-, or 5-minute rest intervals between sets of multi and single-joint resistance exercises. Fifteen resistance trained men (23.6 ± 2.64 years, 76.46 ± 7.53 kg, 177 ± 6.98 cm, bench press [BP] relative strength: 1.53 ± 0.25 kg·kg(-1) body mass) completed 12 sessions (4 exercises × 3 rest intervals), with each session involving 5 sets with 10 repetition maximum loads for the free weight BP, machine leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 14 publications
3
54
0
8
Order By: Relevance
“…Subjects performed a maximum of 5 attempts during each visit. The warm-up before each test consisted of 2 sets of 12 repetitions at 40% of 1-RM self-related load of the BP exercise (Senna et al, 2011).…”
Section: Strength Testmentioning
confidence: 99%
“…Subjects performed a maximum of 5 attempts during each visit. The warm-up before each test consisted of 2 sets of 12 repetitions at 40% of 1-RM self-related load of the BP exercise (Senna et al, 2011).…”
Section: Strength Testmentioning
confidence: 99%
“…In this context, previous studies confirm that longer rest intervals (> 180 seconds) result in a higher number of repetitions performed (6,13,19,22). For instance, Miranda et al (22) observed a lower number of repetitions completed for 60 seconds compared to 180 seconds interset rest intervals when performing 5 upper body resistance exercises at 3 sets of 8RM.…”
Section: Discussionmentioning
confidence: 77%
“…Among these training variables, evidence has suggested that the rest interval between sets affects various acute responses including metabolic (4,5), hormonal (6-9), cardiovascular (10)(11)(12), neuromuscular and perceived ratings of exertion (13,14). Thus, the rest interval between sets can be considered a key variable for resistance training prescription, since it affects distinct acute responses, which in turn could modulate chronic neuromuscular adaptations (8,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…The RPE during a resistance exercise session is greater for shorter rest intervals than for longer rest intervals [31,51,52].…”
Section: Effect Of the Interval Length On The Rpementioning
confidence: 99%
“…The effect of the length of the rest interval on the RPE during a resistance exercise session has been examined [31,51,52]. The RPE during a resistance exercise session is greater for shorter rest intervals than for longer rest intervals [31,51,52].…”
Section: Effect Of the Interval Length On The Rpementioning
confidence: 99%